Main Tasks and Functions of Schools in Indonesia - Turnadi, Tri; Sharma, Mani Ram (PPSDP International Journal of Education, 2022)
The main task of the function of the principal needs to be discussed because it is the spearhead in the development of Indonesian human resources. Interpretation of the applicable education regulations in Indonesia and their implementation is a must. This research uses the literature review method. The research issue taken is about the duties and main functions of the principal in managing the school as an educational institution. Management of educational institutions refers to the eight points of national education standards. The legal jurisdiction for education management is the National Education Standards Act. The duties and main functions of the principal must have derivative regulations that refer to the law. So that there are no deviant actions in school management. The results showed that after being crystallized from various regulations which refer to the management function, namely POAC.